Fibrinogen Reduction and Motor Function Improvement by Hematopoietic Growth Factor Treatment in Chronic Stroke in Aged Mice: A Treatment Frequency Study. Issue 4 (April 2016) - Liu, Yanying; Popescu, Maria; Longo, Sharon; Gao, Mei; Wang, Dongliang; Mcgillis, Sandra; Zhao, Li-Ru
Stroke is a serious medical condition that causes long-term neurological disability in mainly elderly adults worldwide. Lack of therapy to improve functional recovery in the chronic phase of stroke is a major challenge for stroke research. Combining two hematopoietic growth factors, stem cell factor (SCF) and granulocyte-colony stimulating factor (G-CSF), our previous studies have demonstrated the neurovascular restorative efficacy of this treatment in the chronic phase of experimental stroke. Elevated plasma fibrinogen has been thought to serve as a predictor for ischemic stroke. Here we have determined the treatment frequency in reducing plasma fibrinogen and in restoring motor function in aged mice with chronic stroke. Our findings show that SCF + G-CSF treatment in chronic stroke decreases plasma fibrinogen and improves motor function in aged mice. No differences have been found between a 2-week treatment regimen and 7-day treatment in the plasma fibrinogen assay, while the 7-day treatment regimen displays a better recovery pattern with regard to motor function. This study provides new insight into understanding the potential contribution of SCF + G-CSF in both reducing the risk of recurrent ischemic stroke and enhancing stroke recovery.